Building Better Oral Health Habits Through Education - Ika Kusuma Wardani; M. Alfrio Aditama; Nor Najwa; Aida Yanti; Renie Kumala Dewi (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Oral and dental health is an important component of general health and quality of life. Dental caries remains one of the most common oral diseases among school-aged children. This community service project aims to provide oral health education to students of SDN Alalak Tengah 4. This community service project involved 55 students aged 10–14 years. The community service project was conducted by examining dental conditions using the DMF-T index and 20 item questionnaire that assessed oral and dental health knowledge before and after the intervention. The intervention was delivered through health education using posters. The results showed that most respondents were female (60%) and aged 11 years (50.9%). The majority of students were in the very low DMF-T category (45.5%). The questionnaire results showed that students' knowledge increased after the intervention, but there was no significant relationship between the level of oral health knowledge and the DMF-T index. These findings suggest that knowledge only is not sufficient to influence caries status unless accompanied by a positive attitude and consistent oral health practices. Therefore, oral health promotion programs should emphasize not only knowledge improvement but also behavioral changes in daily oral hygiene practices. Keywords: Oral Health, Dental Caries, DMF-T Index, Oral Health Education, School Children.